Soldagem em chapas de aços inoxidáveis superduplex UNS S32750 utilizando o processo arame tubular - Pessoa, Antônio Rodolfo Paulino (2015)
Superduplex stainless steels (SDSS) may be defined as a family of steels having a two-phase ferritic-austenitic microstructure and the good mechanical properties and high corrosion resistance of this alloy are attributed to this microestrutural balance. These excellent qualities attribute to SDSS great employability in the oil sector, where manufacturing and equipment maintenance are performed by welding, which if not executed properly, can have a negative effect on the metallurgical properties and this problem becomes more critical in multipass welding due to repeated thermal cycles. Among the several welding processes employed in the welding of SDSS, fell to this work was to evaluate the FCAW process in multipass welding joints of SDSS UNS S32750, regarding the selection of appropriate welding parameters and the influence of these parameters on microstructural transformations, mechanical properties and corrosion resistance of welded joints. Then, this work was divided into three steps: Stage 1 was the characterization of the base metal in as-received condition. In Stage 2, weldings were accomplished using a bead on plate (BOP) technique to determine the control factors and their levels to be used in the subsequent stage, in which an experimental design was conducted by Taguchi method with Alloy, Stick out, Shielding gas, welding gun orientation, Arc oscillation, Energy technique and Heat input used as control factors and quality characteristics were evaluated the ratio R/L, bead penetration, ferrite content and inclusions content and microhardness. Finally, in Stage 3 were performed multipass welding in joints and afterwards was executed: A microstructural characterization in three regions of Fusion Zone (Root, Filler and Cap) and Heat Affected Zone by Optical Microscopy (OM) and Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Spectroscopy (EDS) and were also performed a measurement of the ferrite content; measurement of inclusions content; microhardness tests and Critical Temperature Pitting (CPT) tests according to ASTM G150. The results showed, ferrite contents ranging from 44% and 54.9% and their highest values were observed when employed the alloy 2507, heat input of 1.6 kJ/mm and pulsed current. The lowest inclusions contents were obtained by using of shielding gas with the mixture of 96%Ar + 4%CO2 (Stage 2) and heat input of 1,6kJ/mm (Stage 3). The microhardness values in FZ of joints were not affected significantly by any of the control factors. Already, the results of CPT tests showed that pits nucleated preferentially within α, at α/γ grain boundaries and at interfaces areas between large diameter inclusions and the metallic matrix and propagated predominantly into α phase. The CPT values ranging from 47 °C to 78 °C, with highest were obtained for the alloy 2507, heat input of 1.6 kJ/mm and continuous current into Root region and for the alloy 2507, heat input of 1.6 kJ/mm and the pulsed current in Filler and Cap regions. From the three regions of FZs, the Root showed the best results with no defects, satisfactory ferrite contents, lowest inclusions contents and highest CPT values